Persistence of southern California giant kelp beds and alongshore variation in nutrient exposure driven by seasonal upwelling and internal waves - Leichter, James J.; Ladah, Lydia B.; Parnell, P. Ed; Stokes, M. Dale; Costa, Matthew T.; Fumo, James; Dayton, Paul K. (Frontiers in Marine Science, 2023)
Kelp beds provide significant ecosystem services and socioeconomic benefits globally, and prominently in coastal zones of the California Current. Their distributions and abundance, however, vary greatly over space and time. Here, we describe long-term patterns of Giant Kelp (Macrocystis pyrifera) sea surface canopy area off the coast of San Diego County from 1983 through 2019 along with recent patterns of water column nitrate (NO3-) exposure inferred from in situ temperature data in 2014 and 2015 at sites spanning 30 km of the coastline near San Diego California, USA. Site-specific patterns of kelp persistence and resilience were associated with ocean and climate dynamics, with total sea surface kelp canopy area varying approximately 33-fold over the almost 4 decades (min 0.34 km2 in 1984; max 11.25 km2 in 2008, median 4.79 km2). Site-normalized canopy areas showed that recent kelp persistence since 2014 was greater at Point Loma and La Jolla, the largest kelp beds off California, than at the much smaller kelp bed off Cardiff. NO3- exposure was estimated from an 11-month time series of in situ water column temperature collected in 2014 and 2015 at 4 kelp beds, using a relationship between temperature and NO3- concentration previously established for the region. The vertical position of the 14.5°C isotherm, an indicator of the main thermocline and nutricline, varied across the entire water column at semidiurnal to seasonal frequencies. We use a novel means of quantifying estimated water column NO3- exposure integrated through time (mol-days m-2) adapted from degree days approaches commonly used to characterize thermal exposures. Water column integrated NO3- exposure binned by quarters of the time series showed strong seasonal differences with highest exposure in Mar - May 2015, lowest exposure in Sep - Dec 2014, with consistently highest exposure off Point Loma. The water column integrated NO3- signal was filtered to provide estimates of the contribution to total nitrate exposure from high frequency variability (ƒ >= 1 cycle 30 hr-1) associated predominantly with internal waves, and low frequency variability driven predominantly by seasonal upwelling. While seasonal upwelling accounted for > 90% of NO3- exposure across the full year, during warm periods when seasonal upwelling was reduced or absent and NO3- exposure was low overall, the proportion due to internal waves increased markedly to 84 to 100% of the site-specific total exposure. The high frequency variability associated with internal waves may supply critical nutrient availability during anomalously warm periods. Overall, these analyses support a hypothesis that differences in NO3- exposure among sites due to seasonal upwelling and higher frequency internal wave forcing contribute to spatial patterns in Giant Kelp persistence in southern California. The study period includes anomalously warm surface conditions and the marine heatwave associated with the “Pacific Warm Blob” superimposed on the seasonal thermal signal and corresponding to the onset of a multi-year decline in kelp canopy area and marked differences in kelp persistence among sites. Our analysis suggests that, particularly during periods of warm surface conditions, variation in NO3- exposure associated with processes occurring at higher frequencies, including internal waves can be a significant source of NO3- exposure to kelp beds in this region. The patterns described here also offer a view of the potential roles of seasonal and higher frequency nutrient dynamics for Giant Kelp persistence in southern California under continuing ocean surface warming and increasing frequency and intensity of marine heatwaves.